Relating Country Of Origin and Brand Image with Product Purchasing Decisions in Bandung, Indonesia - Salsabila, Delza; Pradana, Mahir (The International Journal of Business Review (The Jobs Review), 2023)
This study attempts to ascertain the degree to which Brand Image and Country of Origin affect Purchase Decisions of Something Products in Bandung City. A quantitative research method was employed. 100 respondents made up the study's sample size. Multiple linear analysis and hypothesis testing are used in this investigation. SPSS 25 was used by the researchers for data processing. The Purchasing Decision Variable (Y) for Something products will increase as a result of the variables Country of Origin (X 1) and Brand Image (X 2), according to the results of the multiple linear analysis. The variables Country of Origin (X 1) and Brand Image (X 2) had a partial influence on Purchase Decision (Y) with t counts of 3.155 and 5.228, respectively. 60.7% of the influence comes from country of origin and brand image, with the remainder coming from other factors.